MENGOPTIMALKAN POTENSI ANAK DI ERA DIGITAL DI SEKOLAH DASAR KECAMATAN KENDURUAN TUBAN: OPTIMIZING CHILDREN’S POTENTIAL IN THE DIGITAL ERA IN ELEMENTARY SCHOOL IN KENDURUAN TUBAN SUB-DISTRICT - Suningsih, Suningsih; Nurilfaza, Ahmad; Sukma, Sukma (PADIMAS, 2024)
The transformation of the digital era provides great opportunities for elementary school students to develop their potential through the integration of technology in the learning process. However, not all schools, especially in the Kenduruan District area, have adequate facilities or understanding to manage technology effectively. This research aims to analyze ways to optimize children's potential in the digital era at the elementary school level. The methods used involve field observations, interviews with teachers, and literature analysis. The results show that technology-based learning can increase student creativity and motivation. In conclusion, it is necessary to increase digital literacy for students and teachers, as well as adequate technological infrastructure support to optimize digital learning in elementary schools in Kenduruan District.